Polyelectrolytes Ability in Reducing Atrazine Concentration in Water: Surface Effects - Mohamad Faiz Mohd Amin; S. G. J. Heijman; S. I. C. Lopes; L. C. Rietveld (The Scientific World Journal)
This paper reports on the direct ability of two positively charged organic polyelectrolytes (natural-based and synthetic) to reduce the atrazine concentration in water. The adsorption study was set up using multiple glass vessels with different polymer dosing levels followed by ultrafiltration with a 1 kDa membrane. The addition of polymers exhibited a capability in reducing the atrazine concentration up to a maximum of 60% in surface-to-volume ratio experiments. In the beginning, the theoretical L-type of the isotherm of Giles’ classification was expected with an increase in the dosage of the polymer. However, in this study, the conventional type of isotherm was not observed. It was found that the adsorption of the cationic polymer on the negatively charged glass surface was necessary and influential for the removal of atrazine. Surface-to-volume ratio adsorption experiments were performed to elucidate the mechanisms and the polymer configuration. The glass surface area was determined to be a limiting parameter in the adsorption mechanism.